Responses of the Phytoplankton Community of a Tropical Reservoir (São Paulo, Brazil) to the Enrichment with Nitrate, Phosphate and EDTA - Henry, Raoul [UNESP]; Tundisi, José Galizia (Wiley, 1983)
The effects of artificial enrichment with nitrate, phosphate and EDTA on the phytoplankton community were studied in the Lobo Reservoir (São Paulo, Brazil). After 14 days of in situ incubation, the amounts of suspended matter and chlorophyll a, the numbers of cells and the carotene/chlorophyll ratio were determined. The addition of nitrate and phosphate to water samples produced significant effects on the chlorophyll a and cell counts, while EDTA acted only on the cell production. Both nitrate and phosphate, when analysed individually, caused a decrease in the value of the carotene/chlorophyll ratio. A synergistic effect of the addition of EDTA and N on the suspended matter was observed. Copyright © 1983 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim
Keywords: enrichment; nitrate; phosphate; phytoplankton; tropical reservoir